THE REFLECTION OF HEROISM IN THE NOVELS OF E. HEMINGWAY - Zarina Abdiyeva; Eldorbek Hamitov Erkinovich (Лучшие интеллектуальные исследования, 2024)
This article critically examines the theme of heroism in the novels of E. Hemingway, exploring how his characters navigate challenges and confrontations with courage and resilience. Focusing on key works such as "The Old Man and the Sea" and "For Whom the Bell Tolls," it delves into the complexities of heroism portrayed by Hemingway, shedding light on the enduring significance of his literary representations of bravery, sacrifice, and human endurance.